2017
DOI: 10.1371/journal.pone.0179356
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting academic and lay press print coverage of the 2013-2016 Ebola Virus Disease outbreak

Abstract: Under a traditional paradigm, only those with the expected background knowledge consume academic literature. The lay press, as well as government and non-government agencies, play a complementary role of extracting findings of high interest or importance and translating them for general viewing. The need for accurate reporting and public advising is paramount when attempting to tackle epidemic outbreaks through behavior change. Yet, public trust in media outlets is at a historic low. The Crisis and Emergency R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 134 publications
0
6
0
Order By: Relevance
“…In line with CERC predictions, both perceived efficacy as well as perceived threat were associated both with information seeking and protective behavior. Other experimental studies presented CERC as a broad foundational framework, but investigated Among the other 16 research reports in which CERC played a major role, a large portion used CERC principles as presented in the CERC Manual to evaluate adequacy of news coverage, tweets, and other public health responses during a specific crisis (Kieh et al, 2017;Maguire et al, 2016;Nour et al, 2017;Ophir, 2018;Panagiotopoulos et al, 2016;Thomas et al, 2016). For example, Maguire and colleagues developed a coding scheme based on the CERC Manual and evaluated the extent to which certain components of effective communication were more present than others in Department of Veterans Affairs infection control lapse incidents between 2009 and 2012.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with CERC predictions, both perceived efficacy as well as perceived threat were associated both with information seeking and protective behavior. Other experimental studies presented CERC as a broad foundational framework, but investigated Among the other 16 research reports in which CERC played a major role, a large portion used CERC principles as presented in the CERC Manual to evaluate adequacy of news coverage, tweets, and other public health responses during a specific crisis (Kieh et al, 2017;Maguire et al, 2016;Nour et al, 2017;Ophir, 2018;Panagiotopoulos et al, 2016;Thomas et al, 2016). For example, Maguire and colleagues developed a coding scheme based on the CERC Manual and evaluated the extent to which certain components of effective communication were more present than others in Department of Veterans Affairs infection control lapse incidents between 2009 and 2012.…”
Section: Resultsmentioning
confidence: 99%
“…A systematic review cannot definitively determine why something has not been empirically tested. However, the fact that a large proportion of the investigations of CERC consist of content analyses of news coverage through stages of crises (Kieh et al, 2017;Maguire et al, 2016;Nour et al, 2017;Ophir, 2018;Panagiotopoulos et al, 2016;Thomas et al, 2016) suggests that researchers have found the stage elements of the model more useful in highly applied settings as a standard for retrospective critique than as a predictive tool about the outcomes of that messaging. Furthermore, all of these studies assessed news coverage over the life of a crisis by comparing them to CERC as presented in CDC publications like the CERC Manual (U.S. Department of Health and Human Services [HHS] and CDC, 2018), rather than measuring against Veil et al 's (2008) formal propositions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, perception drives behaviour more readily than facts. Furthermore, most citizens are not sourcing their information from academic scholarship, but rather rely on the mass media to translate key findings into an accessible format 16. With regard to concerns about biosecurity and the threat of bioterrorism, Caduff notes that:…”
Section: Motivating Preventive Behavioursmentioning
confidence: 99%
“…In his article ‘The plague of ideas’, Ralph Peters claims ‘ideas can now travel more swiftly than any human being–or disease’ 21. One of the problems with this is that the ideas being circulated about epidemics are rarely communicated by researchers directly, potentially leading to public misinterpretation of disease risk 16. According to risk-theorist Francois Ewald,22 the concept of ‘risk’ is socially constructed, meaning the label is dependent on collective human judgement.…”
Section: Motivating Preventive Behavioursmentioning
confidence: 99%